Fiscal sustainability of the German Laender: Time series evidence - Heiko T. Burret; Lars P. Feld; Ekkehard A. Köhler (Albert-Ludwigs-Universität Freiburg, Institut für Allgemeine Wirtschaftsforschung, Abteilung für Wirtschaftspolitik und Ordnungsökonomik, 2015)
We analyze the sustainability of public finances in the 16 states (Laender) of the Federal Republic of Germany using an unprecedentedly comprehensive fiscal dataset covering the period from 1950 to 2011 for West German Laender and from 1991 to 2011 for East German Laender. As we apply unit root and stationarity tests not only on debt but also on expenditure and revenue and explore their long-run relation in cointegration analyses for each Land we extend the existing literature. The results provide evidence against strict fiscal sustainability in a majority of German Laender. A notable exception to this finding is Bavaria.
Keywords: H62; H77; H72; 330; Fiscal Sustainability; Federalism; Unit Root; Cointegration; Public Debt